Catalytic properties of γ-Al2O3 supported Pt–FeOx catalysts for complete oxidation of formaldehyde at ambient temperature. Issue 126 (10th December 2015) - Cui, Weiyi; Yuan, Xiaoling; Wu, Ping; Zheng, Bin; Zhang, Wenxiang; Jia, Mingjun
Abstract : A Pt–FeO x /Al2 O3 catalyst with suitable Fe/Pt ratio showed excellent catalytic activity and stability for complete oxidation of formaldehyde at ambient temperature. Abstract : A series of γ-Al2 O3 supported Pt–FeO x catalysts (Pt–FeO x /Al2 O3 ) with different Fe/Pt atom ratios were prepared, and their catalytic properties were investigated in the oxidation of formaldehyde. It was found that the catalytic activities of Pt–FeO x /Al2 O3 catalysts are varied with the change of Fe/Pt ratios. Among them, the sample with a Fe/Pt ratio of 1.0 exhibits the highest activity, which can efficiently convert formaldehyde to CO2 at ambient temperature. The catalytic activity of the Pt–FeO x /Al2 O3 catalyst can be further improved by the addition of water vapor into the feed stream. A variety of characterization results showed that both Pt nanoparticles and FeO x species are highly dispersed on the surface of the γ-Al2 O3 support. Changing Fe/Pt ratios could influence the chemical states and the redox properties of Pt and Fe species. The catalysts with appropriate Fe/Pt ratios have more accessible active sites, i.e., the Pt–O–Fe species, which are located at the boundaries between FeO x and Pt nanoparticles, thus showing high activity for the oxidation of formaldehyde under ambient conditions.